Origins of the warfare state - Boggs, Carl, author.
1 online resource
Keywords: "The post-World War II emergence of a full-blown state of perpetual war is arguably the most important feature of contemporary American politics. This book examines the 'warfare state' in terms of a broad ensemble of structures, policies, and ideologies: permanent war economy, national security-state, global expansion of military bases, merger of state, corporate, and military power, an imperial presidency, the nuclear establishment, and superpower ambitions. Carl Boggs makes the argument that the 'Good War' led to an authoritarian system that has expanded throughout the post-war decades, undermining liberal-democratic institutions and values in the process. He goes on to suggest that current American electoral politics show no sign of rolling back the warfare state and, in fact, may push it to a new threshold bordering on American fascism"--Publisher description.